The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.jamcollsurg.2007.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Shock and Resuscitation-Mediated Tissue Water Distribution is Normalized by Adjunctive Peritoneal Resuscitation

Abstract: BACKGROUND-Adjunctive direct peritoneal resuscitation (DPR) from hemorrhagic shock (HS) improves intestinal blood flow and abrogates postresuscitation edema. HS causes water shifts as a result of sodium redistribution and changes in transcapillary Starling forces. Conventional resuscitation (CR) with crystalloid aggravates water sequestration. We examined the compartment pattern of organ tissue water after HS and CR, and modulation of tissue edema by adjunctive DPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
1
19
1
Order By: Relevance
“…The benefits reported in this animal modelbased research included instantaneous and sustained increases in mesenteric microvascular perfusion (arterioles and capillaries alike) [4,5]. In addition, they demonstrate restoration of premucosal A3 arteriolar endothelial cell receptor-dependent dilator function [4], avoidance of endothelial cellular edema [4] and tissue edema [6], decreases in resuscitation gut lymph flow and gut lymph concentrations of inflammatory cytokines and hyaluronic acid (a structural glycoprotein involved in regulation of tissue hydration) [7], and decreases in rat mortality [8]. They call this technique "direct peritoneal resuscitation" and have done considerable work toward delineating the vascular response mechanisms involved.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The benefits reported in this animal modelbased research included instantaneous and sustained increases in mesenteric microvascular perfusion (arterioles and capillaries alike) [4,5]. In addition, they demonstrate restoration of premucosal A3 arteriolar endothelial cell receptor-dependent dilator function [4], avoidance of endothelial cellular edema [4] and tissue edema [6], decreases in resuscitation gut lymph flow and gut lymph concentrations of inflammatory cytokines and hyaluronic acid (a structural glycoprotein involved in regulation of tissue hydration) [7], and decreases in rat mortality [8]. They call this technique "direct peritoneal resuscitation" and have done considerable work toward delineating the vascular response mechanisms involved.…”
Section: Discussionmentioning
confidence: 83%
“…Over the past decade, Garrison and colleagues have reported local and systemic benefits and the mechanisms involved after the serosal exposure of the intestines to 2.5% dextrose clinical dialysis solution (Delflex, Fresenius Medical Care, Walthum, MA, USA) used as adjunctive treatment with conventional resuscitation after hemorrhagic shock [4][5][6][7][8][9]. The benefits reported in this animal modelbased research included instantaneous and sustained increases in mesenteric microvascular perfusion (arterioles and capillaries alike) [4,5].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies demonstrated that endorgan injury and subsequent MODS result from a cause-effect relationship between three pathophysiologic events, which likely interact in a time-dependent, tissue-specific fashion. First, a persistent and progressive splanchnic vasoconstriction and hypoperfusion leading to relative ischemia/hypoxia [26,27]; Second, a gut-derived systemic inflamematory response generated by the ischemic gut [28]; and third, inevitable fluid shifts at both the cellular level due to ionic-disequilibrium and at the capillary level due to alteration of the trans-capillary Starling forces that govern fluid exchange [29,30].…”
Section: Animal Modelsmentioning
confidence: 99%
“…This splanchnic and distant organ hyperperfusion was associated with downregulation of the systemic inflammatory response and an increase in survival compared with conventional resuscitation therapies. 16,18 Recent studies [19][20][21] have noted that postresuscitation tissue neutrophils infiltration, which is tissue and time dependent, cellular edema, and capillary perfusion regulated by hydrogen and potassium membrane transport and water compartment distribution are all normalized by DPR with hypertonic peritoneal dialysis fluid.…”
Section: E S P I T E a D V A N C E S I Nmentioning
confidence: 99%